Analysis of Rural and Urban Land and Building Tax Collection and Accounting Recording (PBB-P2) in North Bolaang Mongondow Regency - Salamun, Nurfazria; Sabijono, Harijanto; S. E. Mintalangi, Syermi (Formosa Journal of Applied Sciences, 2024)
Starting from the ratification of Article 28 of the Regional Law, it has the ability to collect PBB-P2 tax thanks to the 2009 Regional Tax and Levy Law. The transfer of PBB-P2 as a regional tax is expected to boost PAD, improve community services, perfect the APBD framework, and increase accountability and transparency in its implementation. . Determining the collection and documentation of PBB-P2 accounting is the aim of this research in Bolaang Mongondow Regency, North. This research uses descriptive qualitative methodology. The findings of this study indicate that although PBB-P2 tax collection as a whole, this institution functions efficiently and complies with relevant laws there are still a number of obstacles that hinder the process, one of which is the continued non-compliance and non-compliance of PBB-P2 taxpayers. lack of awareness of their tax obligations. PBB-P2, incorrect SPPT, relocation of taxpayers outside North Bolaang Mongondow Regency, and lack of personnel to supervise PBB-P2.